Ko, ningo, luego: an enactive approach to the emergence of an epistemic subsystem in jopara (Signifiances (Signifying), 2017)
RésuméLa situation de contact étroit et prolongé que connaissent les deux langues co-officielles du Paraguay, l’espagnol et le guarani, a contribué à l’émergence de parlers dits "jopara" qui se caractérisent par l’alternance d’unités provenant de chacune des deux langues. Nous proposons dans ce travail d’envisager l’alternance, en espagnol jopara, des marqueurs discursifs ko, ningo (tous deux d’origine guarani) et luego (d’origine espagnole) comme la manifestation d’un nouveau sous-système épistémique fondé sur la réanalyse d’opérateurs cognitifs "biomécaniquement incarnés" (Bottineau 2012), lesquels s’insèrent dans un réseau sémiologique qui transcende ce seul champ sémantique. Notre corpus est constitué d’extraits de forums de discussions du Journal Hoy (en ligne), propriété du groupe Multimedia situé à Asunción (Paraguay).AbstractParaguay’s two co-official languages, Spanish and Guarani, have experienced close, extended contact. This has contributed to the emergence of dialectal variants known as "Jopara", in which units from both languages alternate. In this article, we put forth the view that the alternation, in Jopara Spanish, of the discourse markers ko, ningo (both of Guarani origin), and luego (from Spanish) is the manifestation of a new epistemic subsystem based on the reanalysis of "biomechanically embodied" cognitive operators (Bottineau 2012), which are incorporated into a semiological network that transcends this semantic field alone. Our corpus is composed of excerpts from the online discussion forums of the newspaper Hoy, which belongs to the Multimedia group located in Asunción (Paraguay).
Keywords: Enaction; Interlocution; Language contact; Spanish Jopara; Submorphemes; Embodied cognition